Partially neutralized polyacrylic acid as an efficient binder for aqueous ceramic-coated separators for lithium-ion batteries - Thang, Ai Qin (2023)
A partially neutralized polyacrylic acid (Pn-PAA) is used for coating sub-micron-sized α-alumina on a conventional microporous polyolefin separator, fabricating a ceramic-coated separator (CCS). Pn-PAA acts as a dispersant and binder by adsorbing itself on alpha(α)-alumina surfaces under acidic condition through the columbic interaction, providing a repulsive force to disperse fine alumina in aqueous suspension, and binds alumina strongly on plasma-treated separator through hydrogen bonding. This CCS shows favorable wettability in carbonate-based liquid electrolyte and ionic conduction due to the high hydrophilicity of Pn-PAA and alumina. With that, this study found that Pn-PAA-made-CCS yields a substantial adhesion strength of ~106 N/m with enhanced cycle stability, a specific capacity of 145.0 mAh/g after 200 cycles at 1 C at room temperature in half cells (LFP/Li metal).